2021
DOI: 10.1038/s41598-021-84122-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipid, fatty acid, carnitine- and choline derivative profiles in rheumatoid arthritis outpatients with different degrees of periodontal inflammation

Abstract: Rheumatoid arthritis (RA) and periodontitis are chronic inflammatory diseases with several pathogenic pathways in common. Evidence supports an association between the diseases, but the exact underlying mechanisms behind the connection are still under investigation. Lipid, fatty acid (FA) and metabolic profile alterations have been associated with several chronic inflammatory diseases, including RA and periodontitis. Mitochondria have a central role in regulating cellular bioenergetic and whole-body metabolic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…This suggested that acylcarnitine might play an important role in the link between OA and metabolic diseases or cardiovascular diseases, and the potential mechanism is likely related to the β-oxidation of fatty acid metabolism in mitochondria. In addition, studies have shown that acylcarnitine metabolism was significantly related to the progression of another arthritis disease, rheumatoid arthritis (RA) [ 28 , 29 ]. In the study conducted by Beyer et al on the serum of 78 RA patients, they found that the changes in mitochondrial function related to the inflammatory state in RA disease may be related to the metabolism of acylcarnitine [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that acylcarnitine might play an important role in the link between OA and metabolic diseases or cardiovascular diseases, and the potential mechanism is likely related to the β-oxidation of fatty acid metabolism in mitochondria. In addition, studies have shown that acylcarnitine metabolism was significantly related to the progression of another arthritis disease, rheumatoid arthritis (RA) [ 28 , 29 ]. In the study conducted by Beyer et al on the serum of 78 RA patients, they found that the changes in mitochondrial function related to the inflammatory state in RA disease may be related to the metabolism of acylcarnitine [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that acylcarnitine metabolism was significantly related to the progression of another arthritis disease, rheumatoid arthritis (RA) [ 28 , 29 ]. In the study conducted by Beyer et al on the serum of 78 RA patients, they found that the changes in mitochondrial function related to the inflammatory state in RA disease may be related to the metabolism of acylcarnitine [ 28 ]. Andonian et al showed in the study of 48 RA patients that the abnormal metabolism of long-chain acylcarnitine may be an internal link between RA inflammation and cardiometabolic comorbidities [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Beyer et al [ 60 ], the total concentration of FAs was higher in patients with active RA than in those in remission ( p = 0.047). Similarly, RA patients treated with prednisolone had a higher total concentration of FAs as compared to those who did not receive prednisolone ( p = 0.043).…”
Section: The Role Of Fatty Acids In the Treatment Of Ramentioning
confidence: 98%
“…The relationships between RA and periodontitis include similarities in genetic risk factors and immunopathogenesis, pathological mechanisms of chronic inflammation and bone destruction as well as increased production of cytokines, prostaglandins and matrix‐degrading enzymes (Beyer et al, 2021; Bolstad et al, 2020; Janssen et al, 2013; Rutger Persson, 2012; Stabholz et al, 2010). Among the shared risk factors, cigarette smoking is the most prominent (Klareskog et al, 2006; Papapanou et al, 2018; Razali et al, 2005; Tomar & Asma, 2000).…”
Section: Introductionmentioning
confidence: 99%